Drivers of Impulsive Buying in Live Streaming E-Commerce: The Roles of Scarcity, Uniqueness, Anxiety, and Time Pressure - Binarin Tirto Andika; Bayu Novrianda (Riviera Publishing, 2026)
This study examines impulsive buying behavior in live-streaming e-commerce, a rapidly growing digital shopping model that integrates real-time product demonstrations, consumer interaction, entertainment elements, and promotional stimuli. The background of this research is based on the increasing role of live-streaming commerce in shaping consumer purchasing decisions, particularly when consumers are exposed to scarcity appeals, product uniqueness, anxiety, and time-limited offers. This study aims to analyze the effects of scarcity, uniqueness, anxiety, and time pressure on impulsive buying behavior among consumers who have made transactions through live-streaming platforms. A quantitative approach was employed using survey data collected through Google Forms. Among 324 respondents, 213 met the research criteria and were included in the analysis using SPSS. The research instruments consisted of demographic questions and Likert-scale items designed to measure the study variables. The results show that uniqueness, anxiety, and time pressure have positive and significant effects on impulsive buying behavior, whereas scarcity has a positive but insignificant effect. Time pressure emerged as the strongest predictor, followed by anxiety and uniqueness. These findings indicate that impulsive buying behavior in live-streaming commerce is influenced more by psychological urgency, emotional tension, and perceived product distinctiveness than by scarcity appeals alone. The study concludes that marketers should manage time pressure and emotional cues ethically to encourage responsible consumer engagement.